Tingkat Pengetahuan Kesehatan Reproduksi dan Sikap Terhadap Seks Pranikah Pada Mahasiswa Biologi Jurusan Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar - Muflihana, Muflihana; Azis, Andi Asmawati; Taiyeb, A.Mushawwir (Universitas Negeri Makassar, 2018)
Abstract. The aim of this experiment is to determine the level of knowledge of reproduction health and attitude toward premarital sexual for Biology Students in State University of Makassar. This experiment has model of descriptive experiment with simple survey method. The subject of this experiment is Biology Student in State University of Makassar by using of non probability sampling technique with convience sampling method and amount of sample is 45 respondences. The collected data from the level of knowledge of health reproduction and attitude toward premarital sexual analyze by using qualitative analysis technique with calculate the frequencies and percentage. The result of this experiment from the level of knowledge of reproduction health is in good category with percentage of 75,6%, and the result of attitude toward premarital sexual is mostly declineÂ with 91,1% of percentage. Based on the analysis we can conclude that the level of knowledge of reproduction health of Biology Student in State University of Makassar has good level, and their attitude toward premarital sexual does not support it.Keywords: level of knowledge, reproduction health, premarital sexual, attitude